Time is of the essence: an observational time-motion study of internal medicine residents while they are on duty - Leafloor, Cameron; Liu, Erin (Yiran); Code, Cathy; Lochnan, Heather; Keely, Erin; Rothwell, Deanna; Forster, Alan; Huang, Allen (Canadian Medical Education Journal, 2017)
Background: The effects of changes to resident physician duty hours need to be measureable. This time-motion study was done to record internal medicine residents’ workflow while on duty and to determine the feasibility of capturing detailed data using a mobile electronic tool. Methods: Junior and senior residents were shadowed by a single observer during six-hour blocks of time, covering all seven days. Activities were recorded in real-time. Eighty-nine activities grouped into nine categories were determined a priori. Results: A total of 17,714 events were recorded, encompassing 516 hours of observation. Time was apportioned in the following categories: Direct Patient Care (22%), Communication (19%), Personal tasks (15%), Documentation (14%), Education (13%), Indirect care (11%), Transit (6%), Administration (0.6%), and Non-physician tasks (0.4%). Nineteen percent of the education time was spent in self-directed learning activities. Only 9% of the total on duty time was spent in the presence of patients. Sixty-five percent of communication time was devoted to information transfer. A total of 968 interruptions were recorded which took on average 93.5 seconds each to service. Conclusion: Detailed recording of residents’ workflow is feasible and can now lead to the measurement of the effects of future changes to residency training. Education activities accounted for 13% of on-duty time.